(3OjhGf GHf GdQheis - (3Ydj Hf GdYHGS Hf LQjL, Ch LhQLjS, GdQhej, CHh GdMSf,J (B283 (3g` s ((3YHOGdQMef Hf CMeO Hf YHGS s)
(3BNQgG (B:s
(3JfJgi HHYV bGajI GdOGd s
(3LeYg CMO GdaVdGA hbOe dg HebOeI PcQ ajgG Cf GdfGS CONdhG ai TYQg eG djS efg hCfg gPHg ef Pdcs
(3cJHJ HQSe NRGfI YeGO GdOjf OGhO Hf YRGdOjf GdQGhOis
(3fSNI QGHYIs
(3hQOJ JMJ Qbe (B2191s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdCOHs